"Bringing Your Whole Self to Research": The Power of the Researcher's Body, Emotions, and Identities in Ethnography. Issue 1 (25th October 2018) - Hordge-Freeman, Elizabeth
Despite advancements, there remains relatively little research about how researchers navigate their bodies and emotions in the context of field research. Perhaps because it represents a threat to ideas about objective or value-free research, qualitative researchers may receive the least amount of practical training about how their bodies and emotions matter in the field. The prevailing assumption is that researchers will eventually find their way or organically develop the pivotal relationships that they need to conduct their work. This uncertainty can be a tremendous source of anxiety for researchers new to the field and even for those seasoned researchers initiating new projects. In this article, I explore the factors that shape the meanings that research participants attach to researchers' bodies and emotions and, similarly, how researchers' emotions are implicated in their research. Drawing on constructivist grounded theory and critical feminist methodologies, I use specific examples from my ethnographic research in Brazil to highlight the complex and contradictory ways that researchers' bodies and emotions are perceived by potential research participants and can be managed in order to enhance ethnographic research. Ultimately, this presentation is intended to explore the challenges and possibilities created when researchers marshal their bodies and emotions to bring their whole self to research.